Theory of Planned Behavior and Health Belief Model on Factors Associated with Breast Self Examination among University Students - Asruria Sani Fajriah; Supriyadi Hari Respati; Bhisma Murti (Masters Program in Public Health, Sebelas Maret University, 2019)
Background: The new cases of breast cancer worldwide are estimated at 1,384,155 with almost 459,000 related deaths. A common problem for breast cancer treatment is patients who often come to a health care provider when they are in the final stages of cancer. Early detection of breast cancer can be conducted by using the method of Breast Self Examination (BSE). This study aimed to analyze the determinant of Breast Self Examination (BSE) in female university students.Subjects and Method: This study used a cross sectional design. This study was conducted at Universitas Sebelas Maret, Surakarta, Central Java, from August-September 2019. A sample of 200 female university students was selected by simple random sampling. The dependent variable was Breast Self Examination. The independent variables were age, perceived barrier, self-efficacy, subjective norm, and attitude. The data were collected by using questionnaires. The data were analyzed by a multiple logistic regression run on Stata 13.Results: Breast Self Examination (BSE) increased with age ≥20 years (OR=5.01; 95%CI=1.79 to 14.00; p=0.002), positive perceived barrier (OR=0.0CI8;95%=0.03 to 0.27; p<0.001), strong self-efficacy (OR=6.40; CI 95%=2.53 to 16.23; p<0.001), strong subjective norm (OR=4.13; 95%CI= 1.55 to 10.99; p=0.004), and positive attitude (OR=7.55; 95%CI= 2.57 to 22.22; p=0.022).Conclusion: Breast Self Examination (BSE) increased with age, perceived barrier, self-efficacy, subjective norm, and attitude.Keywords: breast cancer, breast self examination, theory of planned behavior, screeningCorrespondence: Asruria Sani Fajriah. Masters Program in Public Health, Universitas Sebelas Maret. Jl. Ir. Sutami 36A, Surakarta 57126, Central Java. Email: sanifajriah@gmail.com. Mobile: +6285790341801.Journal of Health Promotion and Behavior (2019), 4(4): 246-257https://doi.org/10.26911/thejhpb.2019.04.04.01